Assessment of post-harvest fish losses at the fishers’ level in Lake Tana, Ethiopia - Solomon Birie; Minwyelet Mingist; Mulugeta Kibret (Fisheries and Aquatic Sciences)
Fish are essential for ensuring food and nutrition security; and economic growth. However, post-harvest loss poses a significant challenge in the value chain due to the perishable nature of fish. This study aimed to address the information gap on post-harvest fish losses at the fishers’ level in Lake Tana. Data were collected through direct field observation, questionnaire-based loss assessment, and load-tracking methods. Assessment results revealed that fishers incur three types of losses, namely: physical, quality, and market forces, at different points in the value chain. The main causes of loss were identified as delays in net hauling, poor post-harvest handling, and the absence of a market for open sun-dried fish. An average of 1.45 ± 0.51 kg of raw fish loss was estimated per fishing trip. The physical loss of raw fish resulted in an annual loss of 5,121.85 Ethiopian Birr ($102.43) per fisher, representing a total percentage loss of 6.32%. The estimated annual mean financial losses due to both physical and quality-related factors in dried fish products were valued at 1,178.5 Ethiopian Birr ($23.57), representing 11.32% of their total income. To mitigate the extent of post-harvest losses, the fishers used different methods, like drying poor-quality fish rather than discarding it. The findings of this study revealed that post-harvest fish loss was not as severe as compared to other water bodies in Ethiopia. This is a good trend showing proper resource utilization to ensure food security, where other fishers from different parts of the country can learn from.